Total Knee Arthroplasty following Genicular Artery Embolization: A Case Report - G Varun Prasad; Mohammad Salil; Jai Thilak (Journal of Orthopaedic Case Reports)
Introduction: The literature on total knee arthroplasty following genicular artery embolization (GAE) is still in its early stages. This case highlights the challenges and essential considerations in performing total knee arthroplasty for advanced osteoarthritis (OA) in patients who experience inadequate pain relief following GAE. Case Report: A patient with advanced OA underwent GAE for knee pain. He had swelling and skin discoloration around the knee, which required readmission. The patient sought further treatment options due to persistent knee pain. After a thorough pre-operative vascular assessment, he underwent total knee arthroplasty. At 1-year follow-up, he reported significant pain relief, improved knee range of motion, and returned back to daily routine activities. Conclusion: This case illustrates that after GAE for OA, with no pain relief, a successful total knee arthroplasty can be performed after comprehensive pre-operative workup with counselling on GAE issues.